The organization of scientific culture in Lima: 1890-1930 - Cueto, Marcos (Universidad del Pacífico, 1986)
This study is a social history of the emergence of modern science in Peru. It analyzes the variables that permitted the beginnings of scientific research based in around specialized journals and institutions at the turn of the century. It examines the influence of nonscientific criteria such as Nationalism in the research done on two Peruvian diseases: Verruga and Mal de Altura. Finally, it analizes the social and intellectual factors that restrained a stronger development of peruvian science during the period.